ENTERPRISE ARCHITECTURE DESIGN BLUEPRINT FOR SMART VILLAGE IMPLEMENTATION IN SUMUR BANDUNG SUB DISTRICT (CASE STUDY : SMART LIVING DIMENSION) - Dzaky Muhammad Rafi Permana; Berlian Maulidya Izzati; Fitriyana Dewi (STKIP PGRI Tulungagung, 2022)
Sumur Bandung District is one of Bandung City's sub-districts that provides public services and empowerment to its residents. The sub district faces a number of issues in carrying out its duties and providing services. One of the issues confronting Sumur Bandung Sub District is the lack of Final Waste Processing Sites (TPPAS). With the current waste management model, there will be more garbage piles in TPPAS, causing environmental problems for its resident. As a result, The implementation of one of the dimensions in the smart village, namely smart living, is required. by improving current waste management model and supported by technological innovation. However, technological innovation itself will cause new problems if management is seen only as an activity provision of software/hardware for automation needs. Based on these issues, it is necessary to create a Enterprise architecture design of waste management that aims to align technology strategy with business strategy, TOGAF ADM was chosen as the framework because it provides a method for developing, managing, and implementing enterprise architecture maintenance. The results of the design are in the form of a blueprint that can be used as a reference for Sumur Bandung Sub District to overcome issues.